Changes in root growth and water uptake contribute to the yield and water productivity improvement in winter wheat during the past three decades: A case study in the North China Plain - Haotian Li; Na Liu; Liwei Shao; Xiuwei Liu; Hongyong Sun; Suying Chen; Xiying Zhang (Agricultural Water Management)
Over the past three decades the yield and water productivity (WP) of winter wheat have significantly improved in the North China Plain (NCP). The contribution of root systems to these improvements should be understood to develop future strategies for breeding and field management. Continuous root sampling and soil water monitoring were conducted for a long-term irrigation experiment on winter wheat from 1992 to 2023 at the Luancheng Agroecological Experimental Station in the NCP. Three irrigation treatments were selected to represent different water supply conditions, i.e. severe water deficit (SD, no irrigation), moderate water deficit (MD, irrigation of 120–180 mm) and adequate water supply (AW, irrigation of 240–335 mm). For winter wheat, yield increased averagely by 35.0 %, 35.1 % and 42.9 % on average, and WP increased by 19.2 %, 23.2 % and 19.3 % under SD, MD and AW, respectively, from 1992–2023. Corresponding to the improvements in yield and WP, the total root length (TRL) at maturity was decreased by 6.6 %, 7.8 % and 26.2 % under SD, MD and AW, respectively. The reduction in the root length density (RLD) of the 0–40 cm soil layer was 47.4 %, which corresponded to an increase in RLD of 27.7 % in the 40–100 cm layer and 17.5 % in the 100–200 cm layer on average under the three water supply conditions. Redundant root growth in the shallow soil profile decreased without affecting soil water use in the deep soil layer: the root efficiency in water uptake (RE) continuously increased at a rate of 0.30–0.51 10−3 m3 km−1 yr−1, and the proportion of soil water depletion that contributed to crop evapotranspiration during the reproductive stage of winter wheat increased from 50.9 %–72.8 % in 1992–1999 to 61.1–78.1 % in 2010–2023 under the three water supply conditions. Optimized distribution of seasonal evapotranspiration increased biomass allocation to grains by 30.0 % for SD, 17.5 % for MD, and 27.0 % for AW from the 1992–2023, whereas the root: shoot ratio (R/S) decreased by 17.0 % for SD, 25.3 % for MD and 22.4 % for AW on average. The results suggest that reducing redundant root growth in the shallow soil profile without affecting soil water use in the deep soil profile could result in a relatively high RE combined with relatively low R/S, thereby reducing root carbohydrate consumption and improving the overall yield and WP of winter wheat.